Design and Application Research of Remote Gain Unit based on C＋L Band - LIANG Yudong; YU Jiekui; TAN Man; DUAN Mingxiong; WANG Wenzhong; LONG Han; XU Jian; HUANG Chao; LI Shuheng; WU Jianjun (Guangtongxin yanjiu, 2025)
【Objective】In order to solve the problem of complex and difficult implementation of large capacity and ultra-long haul transmission system in C＋L band, a Remote Gain Unit (RGU) is designed to amplify both C and L bands.【Methods】The article examines the theory of optical signal amplification by Erbium-Doped Fiber (EDF) and derives the relationship between the length of EDF and the gain as well as the noise figure of the RGU. Then, through simulation, the gain and noise factor of the RGU under different design schemes are compared. The best EDF length of C and L bands in RGU is selected, and the optimal performance of the C＋L band RGU based on the Remote Optical Pump Amplifier (ROPA) system is designed by optimizing the parameters of the optical path sub-system. The article also reports on the experimental verification of a single-carrier 400 Gbit/s ultra-large capacity long-span unrepeatered transmission system based on a backward RGU, operating in the C＋L bands.【Results】A new record of 36 Tbit/s (90×400 Gbit/s) repeaterless transmission of 342.5 km is achieved in the experiment by using forward high-order Raman amplification technology and high-order pump combined with backward ROPA amplification technology.【Conclusion】The results show that the gain and noise factor of the experimental C＋L band RGU are highly consistent with the results of the simulation data. The design of the 17 m EDF in the C band and 21 m erbium fiber in the L band under this remote gain structure is consistent with the theoretical research. The transmission records of the experimental system show that the C＋L band RGU designed based on theoretical research is feasible in the non-relay large-capacity transmission system and can greatly improve the transmission distance of the C＋L band transmission system. The experimentally significant results obtained in the article provide experimental evidence for the performance, indicators, parameters, and standards of the system, guiding the expansion of signal bands in the application of high-capacity Ultra-Long-Haul (ULH) systems in China.